A Critique of Iran in the Safavid Era - Behzad Karimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main purpose of this article is to analyze and criticize the ideological ideas of the historiography of Shah Isma'il I Safavid in the book of Iran in the Safavid Era by Ali Akbar Velayati. This book is organized in 656 pages, in one introduction and five chapters, with the aim of examining Iranian history during the Safavid Era. Before attempting to enter the main part of the article, the author has tried to draw up a record of the use of ideological approaches in the history of the Safavid Era. In this way, there are two general and ideological critical and formal approaches that can be explicitly taken from political or religious ideas behind both. From the author's point of view, the history of Iran in the Safavid Era is based on works that can be considered as ideological official works. Given the importance of the Safavid history in two types of critical and official ideological historiography, the author has tried to identify and extract the official ideological agenda in the book, focusing on the period of Shah Isma'il I. In this way, the author, while criticizing the sources of study data, has tried to classify events that have undergone ideological readings based on first-hand resources and then analyze according to the identified agenda.